World-Class PGE-Cu-Ni Talnakh Deposit: New Data on the Structure and Unique Mineralization of the South-Western Branch - Nadezhda Krivolutskaya; Nadezhda Tolstykh; Tatyana Kedrovskaya; Konstantin Naumov; Irina Kubrakova; Oksana Tyutyunnik; Bronislav Gongalsky; Elena Kovalchuk; Larisa Magazina; Yana Bychkova; Anton Yakushev (Minerals, 2018)
The Talnakh deposit is one of the largest PGE-Cu-Ni deposits in the world. It is located inside the North-Western part of the Siberian Trap province and consists of three branches. The problem of massive ore origins has been discussed for several decades. The structure of the South-Western branch and the mineralogy of related its Cu-rich ore are discussed in this article. The Southern-2 orebody has a deep inclination (45°) inside the intrusive body, close to its wall, in contrary to the horizontal orebodies of the North-Eastern branch. Mineral composition of the Southern-2 orebody differs from the composition the other orebodies of the Talnakh intrusion as well. It consists ofchalcopyrite, pentlandite with subordinate cubanite, and pyrrhotite. Its specific feature is a large amount of bornite and chalcocite. These minerals occur in disseminated and massive ores. The ores of the other branches of the Talnakh intrusion have chalcopyrite-pyrrhotite compositions whilethe Southern-2 massive ore is enriched in Cu (19.03–25.8 wt %; Cu/Ni = 3.8–8.6) and PGE: ΣPGE changes from 39.1 to 279 ppm, Pd/Pt = 1.3–32. Twelve minerals of the systems Pd-Sn-Cu, Pd-Pb-Bi, Pd-Ni-As, Au-Ag-Pd-Cu, and intermetallics of the Pt-Fe-Cu-Ni types were discovered in ores, but are also widespread in other orebodies. Isoferroplatinum, sperrilite and cooperitewere not found. The unusual structure and composition of the Southern-2 orebody suggest its origin from a separate magma impulse. The correlation between disseminated and massive ores of the Southern 2 orebody in term of chemical and mineralogical composition is evidence of the formation of massive oresin situ, without displacement along the bottom of the massif.